Fair space? Community relations as a booster for improving resilience - Everdingen, Coline van; Peerenboom, Peter Bob; Giessen, Irene van de; Velden, Koos van der; Delespaul, Philippe A. E. G. (Frontiers in Public Health, 2025)
BackgroundThe opportunities of health and happiness are unequally distributed. Multiple triggers lead to social exclusion and can result in homelessness. Efforts are still failing to counter health inequity. Our ethnographic research explores the social pathways of citizens deprived of a home. How can we sustainably promote fair opportunities for all?MethodsUrgent information needs prompted field research among Dutch homeless service users. In semi-structured interviews, we collected information on health and needs. A transdiagnostic, generic strategy is used. Our focus is on the three themes of recovery (meaning, symptoms, and the social dimension), and their evolution over time. From a human rights perspective, the study examines the interactions between homeless service users and their environments. Case descriptions are added for a better understanding of dynamics.ResultsThe dual snowball sampling resulted in a representative sample of Dutch homeless service users in 2015–2017 (16 facilities, 436 users). The health and needs patterns reveal many interrelations of multiple needs. The user–system interactions uncover a systemic failure to match vital needs of the neediest. The interactions over time expose how social decline occurs and identify opportunities for improvement. The survival strategies show that stress often generates communication barriers, conflict, alienation and neglect. This has a negative impact on the self-image, (in)formal networks and place of users in society. A “deadlocked case” from a local experiment demonstrates how community relations can overcome modern system obstacles, while creating stable conditions for growth.DiscussionDespite abundant care and welfare facilities, many shelter users feel abandoned. Our rights-based ecosystem approach leads to the root causes of unfairness, inherent in the healthcare system and culture. The findings disclose that the resilience of Dutch society suffers (but can withstand) significant erosion. By extension, this applies to modern care systems in high-income countries. Fostering resilience requires meaningful social relationships that offer creative solutions. Exploring dynamics stimulates shared learning in safe and public spaces. Providing networks with concrete tools, the approach can foster a coherent, systematic commitment to enrich fair opportunities and pathways toward thriving.